KEMAMPUAN BERBAHASA ANAK TUNARUNGU YANG MENGGUNAKAN COCHLEAR IMPLANTS (STUDI KASUS DI TK SURABAYA DAN SIDOARJO ) - Wahyuni, Atik (Jurnal Pendidikan Khusus, 2017)
Abstract One of the obstacles of deaf children is the ability to speak. Language skills include listening, speaking, reading, and writing skills. Efforts to overcome these obstacles in the form of the use of tools (ABM) and the installation of cochlear implants. This study aims to determine the language skills of deaf children who use cochlear implants, barriers experienced, as well as the intervention provided. The research used qualitative research approach case study type. Technique of collecting data using observation, interview, documentation study and test. Data analysis techniques use source triangulation, technique, and time. The results showed that the ability to listen and speak initially just by looking at the motion of the lips and has not spoken, now the ability to listen and speak simple sentences, complex and semi-complex can only be heard. The obstacles experienced are concentration problems, and also very active students. Interventions for inclusion in the form of classroom learning, tutoring reading, writing, arithmetic and AVT (Auditory Verbal Therapy). The conclusions of this study is to use cochlear implants language skills of deaf children develop properly in accordance with the curriculum of language skills of deaf children with cochlear implant (adapted from notes Shepheard Center Intermede AVT Course 2013). Keywords: language skills, cochlear implants